Polymorphism in the Yersinia LcrV Antigen Enables Immune Escape From the Protection Conferred by an LcrV-Secreting Lactococcus Lactis in a Pseudotuberculosis Mouse Model - Daniel, Catherine; Dewitte, Amélie; Poiret, Sabine; Marceau, Michaël; Simonet, Michel; Marceau, Laure; Descombes, Guillaume; Boutillier, Denise; Bennaceur, Nadia; Bontemps-Gallo, Sébastien; Lemaître, Nadine; Sebbane, Florent (Frontiers in Immunology, 2019)
Yersinioses caused by Yersinia pestis, Yersinia pseudotuberculosis and Yersinia enterocolitica are significant concerns in human and veterinary health. The link between virulence and the potent LcrV antigen has prompted the latter's selection as a major component of anti-Yersinia vaccines. Here, we report that (i) the Y. pestis/Y. pseudotuberculosis group produces at least five different clades of LcrV and (ii) vaccination of mice with an LcrV-secreting Lactococcus lactis only protected against Yersinia strains producing the same LcrV clade as that of used for vaccination. By vaccinating with engineered LcrVs and challenging mice with strains producing either type of LcrV or a LcrV mutated for regions of interest, we highlight key polymorphic residues responsible for the absence of cross-protection. Our results show that an anti-LcrV-based vaccine should contain multiple LcrV clades if protection against the widest possible array of Yersinia strains is sought.